High-Sensitivity Detection of the Lung Cancer Biomarker CYFRA21-1 in Serum Samples Using a Carboxyl-MoS2 Functional Film for SPR-Based Immunosensors - Chiu, Nan-Fu; Yang, Hao-Tang (Frontiers in Bioengineering and Biotechnology, 2020)
We constructed a novel SPR detection assay using carboxyl-functionalized molybdenum disulfide (carboxyl-MoS2) nanocomposites as a signal amplification sensing film for the ultrasensitive detection of the lung cancer-associated biomarker cytokeratin 19 fragment (CYFRA21-1). The experiment succeeded in MoS2 reacted with chloroacetic acid giving carboxyl-MoS2 as the reaction product. The additional shoulder in the C 1s and O 1s peaks of carboxyl-MoS2, which were increased in X-ray photoelectron spectroscopy, confirmed the presence of O–C=O groups on the surface of the carboxyl-MoS2. Compared to MoS2, the experimental results confirmed that carboxyl-modified MoS2 had improved low impedance and low refractive index. The carboxyl-MoS2-based chip had a high affinity, with an SPR angle shift enhanced by 2.6-fold and affinity binding KA enhanced by 15-fold compared to a traditional SPR sensor. The results revealed that the carboxyl-MoS2-based chip had high sensitivity, specificity, and SPR signal affinity, while the CYFRA21-1 assay in spiked clinical serum showed a lower detection limit of 0.05 pg/mL and a wider quantitation range (0.05 pg/mL to 100 ng/mL). The carboxyl-MoS2-based chip detection value was about 104 times more sensitive than the limit of detection of an enzyme-linked immunosorbent assay (0.60 ng/mL). The results showed that the carboxyl-MoS2-based chip had the potential to rapidly assay complex samples including bodily fluids, whole blood, serum, plasma, urine, and saliva in SPR-based immunosensors to diagnose diseases including cancer.